Communicating leadership in organizations. - Mong, Kok Thong. (2008)
Taking the organisational communication approach, we viewed leadership as a product of symbolic interaction. Examined how a shared symbolic context, necessary for effective communication, was maintained in two organisations using case study and participant-observation methodologies.